English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-10 21:55:54 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

y'(t) = 2t - 4* derivative of ln(t+1) - 0

You must know that derivative of ln t is 1/t,
and since (t+1) has derivative 1 we can treat it as if it were t, so we get
1/(t+1),
which gives
y'(t) = 2t - 4/(t+1)

2007-01-10 22:02:13 · answer #1 · answered by Hy 7 · 0 1

6

2007-01-10 21:59:17 · answer #2 · answered by pjveddergirl 3 · 0 1

.

Derivative of y(t) = dy/dt = d/dt ( t^2 - 4 ln(t+1) - 1 )

= 2t - 4 / t+1

This using the basic derivative formulae:

d/dx ( x^n ) = n * x^(n-1)
d/dx ( ln (ax+b) ) = a / ax + b
d/dx ( constant ) = 0

.

2007-01-10 22:06:12 · answer #3 · answered by Preety 2 · 0 0

y(t)=t^2-4ln(t+1)-1

y'(t) = d/dt(t^2-4ln(t+1)-1)

y'(t) = d/dt(t^2) - d/dt(4ln(t+1)) - d/dt(1)

Formulae to be used:
d/dt (t^n) = n * t^(n-1)
d/dt (ln (at+b)) = a / at + b
d/dt (constant) = 0


d/dt(t^2) = 2*t

d/dt(4ln(t+1)) = 4/(t+1)

d/dt(1) = 0

y'(t) = 2t - [4/(t+1)]

2007-01-10 22:03:17 · answer #4 · answered by Som™ 6 · 0 0

(2t^2 +2t -4)/(t+1)

2007-01-10 22:02:31 · answer #5 · answered by saab m 1 · 0 1

fedest.com, questions and answers